Pengaruh Pelatihan Sehat Jiwa terhadap Pengetahuan Kader Kesehatan Jiwa - Eko Arik Susmiatin; Melani Kartika Sari (Universitas Muhammadiyah Jember, 2021)
AbstractMental disorders are a global health problem that still requires effective treatment. One way to improve the quality of handling people with mental disorders (ODGJ) is by increasing the knowledge of mental health cadres in providing nursing care for people with mental disorders. The purpose of this study was to analyze the effect of mental health training on the knowledge of mental health cadres. The number of respondents in this study were 34 mental health cadres. The research design used was pre-experiment with pre-post test design. The results of statistical tests using the paired T-Test showed a significance level of p = 0.00 with a significance level of α = 0.05. These results indicate that there is an effect of mental health training on the knowledge of mental health cadres. Good knowledge will affect the ability of cadres to treat mental patients and their families.